(untitled) (International Seven Journal of Multidisciplinary, 2025)
This study aimed to analyze, through a literature review, the occurrence of Burnout Syndrome among healthcare professionals, highlighting risk factors, consequences, and coping strategies. This is an integrative review based on the analysis of scientific publications available in the SciELO, LILACS, PubMed, and Google Scholar databases, from 2015 to 2025, in Portuguese, English, and Spanish. The literature indicates that burnout is characterized by emotional exhaustion, depersonalization, and reduced professional accomplishment, being especially prevalent among nurses and nursing technicians. The main risk factors identified include long working hours, emotional overload, direct contact with patients in distress, and lack of institutional support. Studies also show that the pandemic period intensified the syndrome’s prevalence, particularly among professionals working in Intensive Care Units. The consequences go beyond the individual level, affecting the quality of care and increasing absenteeism, turnover, and errors in healthcare services. It is concluded that, despite the growing number of studies on the topic, there is still institutional neglect regarding the mental health of healthcare workers, making it necessary to implement prevention strategies, psychological support, and public policies that prioritize occupational well-being.